Efektivitas Hboost (Hb Booster) terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil di Wilayah Kerja Puskesmas Mantrijeron Kota Yogyakarta - Azzahra, Intan Fatimah; Susilo, Joko; Muslihatun, Wafi Nur (Faculty of Medicine, Universitas Andalas, 2023)
Hboost Â is an innovative hemoglobin booster that accompanies blood-boosting tablets that can help optimize and reduce the side effects of blood-boosting tablets. Objective: To determined the effect of giving Hboost in helping to increase hemoglobin levels during pregnancy in the working area of the Mantrijeron Health Center, Yogyakarta City. Methods: A Quasi-Experimental Design with plans Pretest-Posttest with a Control Group design. The population of this research study was all pregnant women in the working area of the Mantrijeron Health Center, Yogyakarta City. The sampling technique used Purposive Sampling to get a total sample of 30 respondents. Data analysis using analysis independent sample t-test. Results: The average hemoglobin level increase in the experimental group Hboost + iron tablets is 1.693 gr/dL. In comparison, the average hemoglobin level increase in the control group of iron tablets is only Â 0.520 gr/dL. Based on that data, it was found that the average of hemoglobin level increase in the experimental group was higher at 1.173 gr/dL than in the control group. Conclusion: Hboost (Hb Booster) effectively complements blood supplement tablets in increasing hemoglobin levels during pregnancy in the working area of the Mantrijeron Health Center, Yogyakarta City.Keywords: Â anemia, blood supplement tablets, Hboost, hemoglobin levels, pregnant women